PENINGKATAN PENGETAHUAN PELAYANAN PALIATIF KANKER TENAGA KESEHATAN MELALUI PROGRAM PELATIHAN PALIATIF KANKER DI BBPK MAKASSAR - Hajerah; Irwan; Santi Anwar (Andragogi Kesehatan, 2024)
Cancer palliative treatment is an approach that is focused on comfort and improvement of the quality of life of patients who face cancer. The aim is to reduce uncomfortable symptoms and provide holistic support to patients and their families. So it is deemed necessary to increase the quantity and quality related to the knowledge and ability of health workers in hospitals and puskesmas in cancer palliative efforts, one of which is through descriptive analytic research training programs by taking secondary data from the results of training on 61 health workers at BBPK Makassar to see the influence of training on Knowledge of health workers related to cancer palliative care. The results of the analysis are known that there is an increase in knowledge related to cancer palliative care before and after statistically significant training (p <0.001). Increasing the knowledge of health workers through a cancer palliative training program can provide holistic care and support the creation of a better experience for patients in dealing with their illness